A New Keynesian Model with Unemployment - Olivier Blanchard; Jordi Galί (Kiel Institute for the World Economy (IfW), 2006)
We develop a utility based model of fluctuations, with nominal rigidities, and unemployment. In doing so, we combine two strands of research: the New Keynesian model with its focus on nominal rigidities, and the Diamond-Mortensen-Pissarides model, with its focus on labor market frictions and unemployment. In developing this model, we proceed in two steps. We first leave nominal rigidities aside. We show that, under a standard utility specification, productivity shocks have no effect on unemployment in the constrained e?cient allocation. We then focus on the implications of alternative real wage setting mechanisms for fluctuations in unemployment. We then introduce nominal rigidities in the form of staggered price setting by firms. We derive the relation between inflation and unemployment and discuss how it is influenced by the presence of real wage rigidities. We show the nature of the tradeoff between inflation and unemployment stabilization, and we draw the implications for optimal monetary policy.
Keywords: E50; E32; 330; new Keynesian model; labor market frictions; search model; unemployment; sticky prices; real wage rigidities; New-Keynesian Phillips Curve; Ungleichgewichtstheorie; Arbeitslosigkeit; Lohnrigidität; Preisrigidität; Friktionelle Arbeitslosigkeit; Theorie